Splat the Cat for president - Bright, J. E.; Scotton, Rob; Eberz, Robert (New York, NY : Harper Festival, an imprint of HarperCollins Publishers, 2016)
After Splat's elected student-body president, he tries to please everyone and makes promises he can't keep
"Based on the bestselling books by Rob Scotton."
"Based on the creation of Rob Scotton"--Cover
Ages 4-8
Keywords: Splat the Cat (Fictitious character) -- Juvenile fiction; Student government -- Elections -- Juvenile fiction; Splat the Cat (Fictitious character); Student government -- Elections; Fiction; Juvenile works